The ornament of histories : a history of the Eastern Islamic lands AD 650-1041 : the original text of Abû Saʻîd ʻAbd al-Ḥayy Gardīzī /: a history of the Eastern Islamic lands AD 650-1041 : the original text of Abû Saʻîd ʻAbd al-Ḥayy Gardīzī. (2011) - Unknown
No abstract available